With a Little Help from My Friends? Surviving the Lockdown Using Social Networks in Rural South India - Isabelle Guérin; Cécile Mouchel; Christophe Jalil Nordman (South Asia Multidisciplinary Academic Journal)
How have rural populations in India mobilized their social networks in times of forced “social distancing”? Focusing on a rural region in Tamil Nadu, mixing Social Network Analysis, descriptive statistics and qualitative interviews conducted before the lockdown, during the lockdown and its aftermath, this paper shows that kinship ties and caste-based relationships are still used as inescapable economic resources, especially when it comes to surviving in this unprecedented worldwide economic and social crisis. The region under study has undergone profound changes in recent decades, combining the disappearance of agrarian forms of dependency and the strengthening of intra-caste interdependence among the lower-caste group (measured here in terms of homophily and homogeneity) with a focus on access to credit and self-help to access employment. The crisis is putting these social networks to the test. Subsidized food, the main pro-poor measure of the Indian government, prevented famine, even if it did not prevent severe malnutrition. Although kin and caste solidarity played a key role in helping households survive, they did not prevent the resurgence of old forms of patronage.